2014
DOI: 10.1002/jcb.24812
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Immortalized Dairy Goat Male Germline Stem Cells (mGSCs)

Abstract: Male germline stem cells (mGSCs), in charge for the fertility in male testis, are the only kind of adult stem cells that transmit genetic information to next generation, with promising prospects in germplasm resources preservation and optimization, and production of transgenic animals. Mouse male germline stem cell lines have been established and are valuable for studying the mechanisms of spermatogenesis. However, there is a lack of stable mGSC cell lines in livestock, which restricts the progress of transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…In our study, melatonin had none effect of the proliferation of an immortalized CD49f positive dairy goat male germline stem cells (mGSCs-I-SB) [38]. However, we found that melatonin can promote the primary SSC colony formation and promote the proliferation markers expression, this indicated that melatonin may affect goat SSCs indirectly.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study, melatonin had none effect of the proliferation of an immortalized CD49f positive dairy goat male germline stem cells (mGSCs-I-SB) [38]. However, we found that melatonin can promote the primary SSC colony formation and promote the proliferation markers expression, this indicated that melatonin may affect goat SSCs indirectly.…”
Section: Discussionmentioning
confidence: 71%
“…The un-adherent cells were transferred into 12-well plates. SSCs were cultured in Dulbecco's modified Eagle's medium (DMEM/F12, GIBCO, Carlsbad, CA) supplemented with 1% fetal bovine serum (FBS, GIBCO), 10% Knockout serum replacement (KSR, Invitrogen, Carlsbad, CA) medium, 4 mM L-glutamine (Invitrogen), 1% non-essential amino acids (Invitrogen), 100 IU/ml penicillin, 100 IU/ml streptomycin (Invitrogen), 10 ng/ml GDNF, 10 ng/ml epidermal growth factor (EGF), 10 ng/ml basic fibroblast growth factor (bFGF), and 20 ng/ml glial cell line derived neurotrophic factor family receptor alpha 1 (GFRa1) [25]. The cells were cultured at 37 °C in a humidified atmosphere with 5 % CO2 for 3 passages.…”
Section: Methodsmentioning
confidence: 99%
“…We optimized in vitro culture systems for dairy goat mGSCs and have successfully established an immortalized dairy goat mGSC cell line42, enabling the long-term study of dairy goat mGSCs in vitro 424344. In order to maintain pluripotency and reprogramming efficiency of dairy goat mGSCs, we investigate the mGSC biology through Tet1 overexpression, verified the self-renewal and proliferation ability in vivo and in vitro to explore the role of Tet1 in mGSC characters and development potentiality.…”
mentioning
confidence: 99%
“…Hence, we hypothesize that the highly conserved RNA-binding protein is also involved in maintaining the identity of adult SSCs and promotes the self-renewal and proliferation of dairy goat SSCs. To test the hypothesis, we overexpressed Lin28a in mGSCs-I-SB cells41. The expression of the pluripotency factors SOX2 and OCT4 is up-regulated by overexpression of Lin28a.…”
Section: Discussionmentioning
confidence: 99%
“…These cells were primary cells isolated from dairy goat testes that were transduced with SV40 large T antigen and Bmi1 to establish immortalized male goat germline stem cells (GmGSC-I-SB)41.…”
Section: Methodsmentioning
confidence: 99%